2021
DOI: 10.3390/jcm10215075
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of LMNA-Related Cardiomyopathy in 18 Patients and Characterization of Two Novel Variants

Abstract: Dilated cardiomyopathy (DCM) refers to a spectrum of heterogeneous myocardial disorders characterized by ventricular dilation and depressed myocardial performance in the absence of hypertension, valvular, congenital, or ischemic heart disease. Mutations in LMNA gene, encoding for lamin A/C, account for 10% of familial DCM. LMNA-related cardiomyopathies are characterized by heterogeneous clinical manifestations that vary from a predominantly structural heart disease, mainly mild-to-moderate left ventricular (LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Moreover, mutations in the LMNA gene result in severe nuclear abnormalities and a higher risk of thromboembolic complications ( 18 , 19 ). Patients carrying LMNA mutations present more aggressive laminopathies and have higher rates of life-threatening arrhythmias and end-stage heart failure ( 21 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mutations in the LMNA gene result in severe nuclear abnormalities and a higher risk of thromboembolic complications ( 18 , 19 ). Patients carrying LMNA mutations present more aggressive laminopathies and have higher rates of life-threatening arrhythmias and end-stage heart failure ( 21 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have made quantitative measurements of nuclear morphology in DCM patients bearing LMNA mutations. Ferradini et al (2021) [ 11 ] reported increased area and elongation but decreased circularity in leukocyte nuclei from DCM patients bearing LMNA missense mutations (Arg189Gln and Glu317Lys). Consistently, our DCM patient with the Ser431* mutation also showed nuclei with decreased circularity and increased elongation; however, in contrast with the report in missense mutations, nuclear area measurements were higher than in wild-type nuclei ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The hallmark of laminopathies is the presence of nuclear abnormalities in different cell types, including blebs, herniations, and honeycomb-structures [ 9 ]. Leukocytes are one of several cell types that show nuclear morphology alterations in DCM patients with LMNA mutations [ 10 , 11 ]. However, the molecular mechanisms are not fully understood and are most likely explained by a combination of functional effects that are cell/tissue-specific [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We broaden the understanding of interdisease phenotypic variability here by characterizing the global proteomic changes from heterozygous overexpression (mutant and WT) of a nonaggregating (E317 K) 19,20 and two aggregating lamin A mutations (N195 K and Q353 K). 4,21,22 We discovered that there was very little overlap in differentially expressed proteins (DEPs) between any of the mutations; many of which play important roles in cardiac function.…”
Section: ■ Introductionmentioning
confidence: 99%